2004
DOI: 10.1063/1.1641528
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic effect of lead lanthanum zirconate titanate in a layered film structure design

Abstract: This letter reports on the formation of a layered film structure and the highly improved photovoltaic output of the lead lanthanum zirconate titanate (PLZT) employed. The photovoltaic current of the PLZT film per unit width was more than 102 times larger than that of bulk PLZT, while the photovoltaic voltage per unit thickness in the layered film structure was almost the same as that in bulk ceramics. These differences are due to the characteristics of the film structure and configuration of the electrode. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 17 publications
4
69
1
Order By: Relevance
“…41,42 It is clear that FPV effects may become very small when the average internal electric field in FNC is zero. [16][17][18][19][20][21][22][23][24] In this case, the photocurrent is only due to charge transport via diffusion.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 It is clear that FPV effects may become very small when the average internal electric field in FNC is zero. [16][17][18][19][20][21][22][23][24] In this case, the photocurrent is only due to charge transport via diffusion.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…[1][2][3][24][25][26] Both experimental and theoretical works have shown that the FPV effect is different from that in conventional p-n junctions or Schottky barriers of the semiconductors. [18][19][20][21][22][23][24][25][26][27] Although a complete understanding of the physical mechanisms involved in the FPV effect in metal-ferroelectric-metal ͑MFM͒ structures with the shortcircuit boundary conditions has not yet been accomplished, a widely accepted explanation of the photoelectric current is the separation of the photon-generated electron-hole pairs ͑excitons͒ by the internal electric field, [20][21][22][23][24] which also provides the potential difference that drives the photocurrent in the external circuit connected to the ferroelectrics. In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 An unique characteristic of FE-PV devices is that the photocurrent direction can be switched by changing the spontaneous polarization direction of a FE material with the electric eld. To date, the photovoltaic effect has been studied in the lithium niobate (LiNbO 3 ) family, [19][20][21][22][23][24] barium titanate (BaTiO 3 or referred to as BTO), 20 lead zirconate titanate (Pb(ZrTi)O 3 or PZT) family, [25][26][27][28] and bismuth ferrite (BiFeO 3 or BFO) family.…”
Section: Introduction To Ferroelectric Photovoltaic Devicesmentioning
confidence: 99%
“…When the material is illuminated after poling, voltage and current can be generated due to the separation of photo induced electron and holes caused by its internal electric field. This is considered an optical property of the material itself which has potential applications for supplying energy transfer in microelectromechanical systems and optoelectronic devices (Sturman & Fridkin, 1992;Ichiki et al, 2004). The steady current in the absence of applied voltage, called photocurrent, is considered the result of photo carriers and the asymmetric electromotive force induced by near-ultraviolet radiation (Tonooka et al, 1998).…”
Section: Opacity Sensormentioning
confidence: 99%